Engineering sulfur vacancies on Mo-doped nickel sulfide for enhanced electrochemical energy storage. (1st May 2023) - Yan, Caihong; Han, Enshan; Yang, Xiaohui; Hu, Kaishuo; Xu, Huiting; Li, Yudong; He, Yanzhen; Lu, Shun
Abstract: Supercapacitor technology has become a popular topic as one of the energy storage systems. As a promising anode material, nickel sulfide (Ni3 S2 ) is hindered for energy storage applications by its low conductivity and inability to meet the expected capacity. Introducing impurities and surface defects can modulate its electronic structure and thus improving its reaction kinetics and electrical conductivity. Here, we use a one-pot hydrothermal method to import both molybdenum ions and sulfur vacancies simultaneously in Ni3 S2 . The doping of molybdenum and vacancies works in concert to achieve a double optimization effect on the electronic structure. The prepared molybdenum-doped Ni3 S2 (denoted as MNS) electrode in which molybdenum in Ni3 S2 can increase its conductivity. Glycol was also employed as a reducing agent to induce the generation of sulfur vacancies, thus further enhancing the electrochemical performance of the electrode. Compare electrode materials with different doping concentrations to investigate the regulation of molybdenum doping concentration on the optimized electronic structure of nickel sulfide. One of the prepared 0.75-MNS electrodes showed the best electronic configuration relative to the other electrodes, exhibiting an ascendant specific capacity of 1531.2 C g −1  at 1 A g −1 . It is capable of reaching 450 C g −1 even at 50 A g −1 . Furthermore, the hybrid supercapacitor consisting of activated carbon and 0.75-MNS electrodes as cathode and anode offers an energy density of 32.85 Wh kg −1  at 800 W kg −1 with good high longevity.